Correlation of sTfR, Hemoglobin, Serum Iron, and eGFR in Pre-dialysis CKD Patients at Sanglah Hospital - I Nyoman Wande; Dewa Ayu Putu Rasmika Dewi; Ni Ketut Puspa Sari (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2023)
Patients with CKD usually have chronic inflammation and impaired antioxidant systems, which worsen with the degree of renal impairment. Anemia is one of the major complications in pre-dialysis CKD patients Examination of iron status that is commonly done today such as serum iron parameters, ferritin, and transferrin saturation is still influenced by the inflammatory process. As an alternative to assessing iron status, the soluble transferrin receptor (sTfR) is not affected by chronic disease or inflammation. The purpose of this study was to determine the correlation of sTfR, hemoglobin, serum iron, and estimation of glomerular filtration rate (eGFR) in pre-dialysis CKD patients. This research was conducted from February to June 2022 at the Nephrology Outpatient Clinic and Clinical Pathology Laboratory of Sanglah Hospital, Denpasar. This research is an observational analytic study with a cross-sectional study design. The research subjects involved were 61 pre-dialysis CKD patients who met the inclusion and exclusion criteria. The results showed that the research subjects consisted of 54.1% male and 45.9% female. The results of the Spearman correlation test showed a weak significant negative correlation between sTfR levels and serum iron in pre-dialysis CKD patients (r = -0.264; p=0.040), but no significant correlation with hemoglobin (r = -0.116; p=0.372) and eGFR ((r = 0.134; p=0.302). This study showed a significant correlation indicating that an increase in serum sTfR levels would affect a decrease in serum iron, so it could be considered as a marker for the management of iron deficiency anemia in CKD.